Independent Evaluation at the IMF : The First Decade. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2012)
This volume examines how independent evaluation contributes to the legitimacy and effectiveness of the IMF. It describes the evolution and impact of the Independent Evaluation Office ten years after its creation as well as the challenges it has faced. It also incorporates feedback from a wide range of internal and external actors and offers useful insights for international organizations, academics, and other global stakeholders.